2023
DOI: 10.1002/bit.28424
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess in‐line monitoring using Raman spectroscopy and Indirect Hard Modeling (IHM): A simple calibration yields a robust model

Abstract: To increase the process productivity and product quality of bioprocesses, the in‐line monitoring of critical process parameters is highly important. For monitoring substrate, metabolite, and product concentrations, Raman spectroscopy is a commonly used Process Analytical Technology (PAT) tool that can be applied in‐situ and non‐invasively. However, evaluating bioprocess Raman spectra with a robust state‐of‐the‐art statistical model requires effortful model calibration. In the present study, we in‐line monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 44 publications
(131 reference statements)
0
19
0
Order By: Relevance
“…The prediction quality of the Good pH probe was not degraded by the additional spectral superimposing component, since it uses the physics-based IHM for spectral evaluation. A calibrated IHM prediction model can be transferred to a more complex system by extending the model with the respective pure component models [ 34 ]. This transfer does not affect the recently determined calibration factors as long as potential newly occurring nonlinear mixture effects are covered by additional adjustable peak parameters in the model.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The prediction quality of the Good pH probe was not degraded by the additional spectral superimposing component, since it uses the physics-based IHM for spectral evaluation. A calibrated IHM prediction model can be transferred to a more complex system by extending the model with the respective pure component models [ 34 ]. This transfer does not affect the recently determined calibration factors as long as potential newly occurring nonlinear mixture effects are covered by additional adjustable peak parameters in the model.…”
Section: Resultsmentioning
confidence: 99%
“…What remains to be shown is whether the Good pH probe can be successfully applied to more complex bioprocesses beyond enzyme reactions, such as E. coli fermentations. In this regard, our previous study has already demonstrated that the combination of Raman spectroscopy and IHM is capable of monitoring other critical process parameters in glucose to ethanol fermentations by Saccharomyces cerevisiae ( S. cerevisiae ) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations